Life of Yusuf Ziya Pasha and His Bathhouse in Keban - Yıldırım, Selda; Aytaç, İsmail (T.C. Vakıflar Genel Müdürlüğü, 2021)
Qualitative study method is used in this article. The life of Yusuf Ziya Pasha and the Konak Bathhouse, which was one of his endowments, located in the Keban district of Elazığ will be examined with regard to their importance for the Ottoman political history and for the history of Turkish-Islamic art. As a result of the education he received in various fields and his talents, Yusuf Ziya Pasha served in many important positions, mainly as a grand vizier for twice during the reigns of Selim III and Mahmut II. In addition to these characteristics, the Pasha, who had a philanthropic personality, was a respected statesman. He significantly contributed to the Turkish Art as the financer of waqf buildings in Malatya, Keban, Çemişgezek, Erzurum, Trabzon and İstanbul and as the calligraphist of plates decorating his waqf buildings. The Konak Bathhouse, on eof his endowments, has been largely destroyed. Its walls are standing but its dome has collapsed. The Bathhouse reflects the Ottoman architecture of the late 18th century. This structure is examined through its plan, architecture, ornamentation and function and evaluated within its historical context .

Bu makalede nitel çalışma yöntemi kullanılmıştır. Yusuf Ziya Paşa’nın hayatı ve vakfetmiş olduğu eserlerden Elazığ İli Keban İlçesi’nde yer alan Konak Hamamı tanıtılarak, Osmanlı Siyasi ve Türk-İslam Sanatı Tarihi bakımından önemi değerlendirilmiştir. Yusuf Ziya Paşa, çeşitli alanlarda aldığı eğitimler ve kabiliyetinin bir sonucu olarak III. Selim ve II. Mahmut devirlerinde iki kez sadrazamlık olmak üzere birçok önemli görevde bulunmuştur. Bu özelliklerinin yanı sıra hayırsever bir kişiliğe sahip olan Paşa, kurmuş olduğu vakıflar yolu ile Malatya, Keban, Çemişgezek, Erzurum, Trabzon ve İstanbul gibi şehirlerde bani olarak, kendisinin yapmış olduğu hat levha örnekleriyle de Türk Sanatına katkılar sağlamış önemli bir devlet büyüğüdür. Yusuf Ziya Paşa’nın yaptırmış olduğu eserlerden makalemize konu olan Keban’daki konak hamamı büyük oranda tahrip olmuştur. Beden duvarları ayakta olan hamamın kubbe örtüsü tamamen çökmüştür. Hamam, 18. Yüzyıl sonu Osmanlı Mimarisini yansıtmaktadır. Bu yapı planı, malzemesi ve işlevi açıklandıktan sonra dönemi içerisinde değerlendirilmiştir.
Yusuf Ziya Paşa’nın Hayatı Ve Keban’da Yaptırdığı Konak Hamamı